Eurocentrism in World History Textbooks: The Case of Canada - (:unkn) unknown (My University, 2014)
0

This paper investigates how Eurocentrism affects World History textbooks, using examples of Edmonton universities which include the University of Al- berta, Concordia University College, Grant MacEwan University and the King’s University College. In this way, the grave implications of Eurocentrism for the study of World History is demonstrated as well as the impact that this set of beliefs might exert on a field of history which aims to overturn Eurocentrism and privilege cross cultural encounters and global approaches to the past is discovered
Keywords: Din Bilimi